2014
DOI: 10.1007/s00203-014-1013-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of synergistic combination potential of probiotic and bacteriophage against antibiotic-resistant Staphylococcus aureus exposed to simulated intestinal conditions

Abstract: This study was designed to evaluate the combined effect of probiotic Lactobacillus rhamnosus and bacteriophage SA11 on the control of antibiotic-sensitive Staphylococcus aureus (ASSA) and antibiotic-resistant S. aureus (ARSA) under the simulated intestinal conditions. The survivability of ASSA and ARSA were determined in the simulated phosphate-buffered saline (PBS)-, trypticase soy broth (TSB)-, and milk-based gastric juices adjusted to pH 2.0, 3.0, and 5.0 at 37 °C for 30 min. The inhibitory effect of bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…2 b). This is in good agreement with previous study showing most bacteriophages are highly stable at pHs between 4 and 9 [ 17 , 18 ]. The observations suggest that the adsorption rates of Salmonella bacteriophages tested in this study may not be changed at the broad ranges of temperature and pH, which are the important environmental factors for the lytic activity of bacteriophages [ 19 ].…”
Section: Discussionsupporting
confidence: 94%
“…2 b). This is in good agreement with previous study showing most bacteriophages are highly stable at pHs between 4 and 9 [ 17 , 18 ]. The observations suggest that the adsorption rates of Salmonella bacteriophages tested in this study may not be changed at the broad ranges of temperature and pH, which are the important environmental factors for the lytic activity of bacteriophages [ 19 ].…”
Section: Discussionsupporting
confidence: 94%
“…coli O157:H7 was reduced by 3.8 and 0.3 log units, respectively, after 5 and 10 h of incubation in the simulated intestinal conditions treated with free bacteriophages. This observation suggests that the susceptibility of free bacteriophages to intestinal condition decreased with increasing the incubation time, resulting in the loss of lytic activity (Woo & Ahn, ). The encapsulated bacteriophages effectively inactivated the growth of E .…”
Section: Resultsmentioning
confidence: 99%
“…The results of the present investigations are partly comparable to the results of Woo and Ahn (2014) for their examination of a combined use of phage SA11 and a Lactobacillus (Lb.) rhamnosus strain against Staphylococcus aureus for modeled intestinal conditions in vitro at different pH values [61]. Phage SA11 inhibited the growth of antibiotic-sensitive and -resistant S. aureus strains if compared to the control cultures after 10 h, whereas the single use of Lb.…”
Section: Discussionmentioning
confidence: 98%
“…rhamnosus led to an inhibition of the germ density first after 20 h in comparison to the corresponding values of the control culture without phages. Thus, the authors suggested that phage lytic activity was predominant after 10 h of incubation and the antimicrobial activity of LAB after 20 h. The authors described the highest reduction ability for a combined application of phage and LAB after 10 h and 20 h [61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation